Wave solutions of the Benjamin-Bona-Mahony’s Equation In Weighted Sobolev Spaces - Cabracancha Montesinos, Lenin Rolando (2019)
We explore theconformable fractional BBM equation. The question of the center of mass of the wave solution is analyzed with the existence of solution for the Benjamin-Bona- Mahony’ s equation (BBM) in a weighted Sobolev space. Similar results of the center of energy in DNA breathing is observed using Klein Gordon equations and Floquet theory.